MACROECONOMIC DETERMINANTS OF ISLAMIC STOCK PRICES: EVIDENCE FROM ISSI-LISTED ISLAMIC BANKS - Muhammad Rifqi; Barianto Nurasri Sudarmawan (Adisam Publisher, 2025)
The capital market in Indonesia continues to develop with increasing investor interest in stocks, according to data released by KSEI. However, amid the high public interest in both conventional and sharia stocks, stock prices are influenced by various factors such as demand and supply, as well as the economic conditions of a country. Therefore, this research aims to analyze the factors that can affect the stock prices of sharia commercial banks through macroeconomic indicators, namely interest rates, inflation, and exchange rates. The research method employed is quantitative. The data used are secondary data obtained from the official reports of Bank Indonesia, the Financial Services Authority (OJK), and Yahoo Finance for 2019–2023. The analytical technique used is the Vector Error Correction Model (VECM) to examine the long-term and short- term relationships between interest rates, inflation, and exchange rates with the stock prices of sharia commercial banks in the ISSI, utilizing the statistical analysis software E- views 12. The results indicate that in the long term, interest rates do not have a significant influence on the stock prices of sharia commercial banks in either the long or short term. In contrast, inflation has a significantly positive effect on the stock prices of sharia commercial banks in both the short and long term, and exchange rates positively impact the stock prices of sharia commercial banks in both the short and long term. These findings confirm that interest rates are not a primary concern for the stock prices of sharia commercial banks.